Gino Strada (1948-2021) - Giorgio Monti (Emergency Care Journal, 2021)
What should be an Emergency Physician? A doctor and a man accustomed to extreme and courageous choices, able to decide quickly, capable of brilliant intuitions and strong standpoints, guided by great determination, self-awareness, enlightened by deep convictions and clear ideas, and an empathy that allows him to never lose his humanity and always know which side to stand on… I worked and had the privilege of being a friend of a great doctor with these characteristics. [...]